Teaching Strategy in Early Childhood Education: Child-Friendly Classroom Management to Anticipate Bullying Behaviours - Wulan, Sri; Fridani, Lara (Program Studi Magister Pendidikan Anak Usia Dini, 2021)
Bullying behaviour can have a negative impact on a child's physical and psychological health. Bullying in the classroom is a challenge for early-childhood educators. Preschool is the first place outside the home where children face social challenges when interacting with their classmates. Child-Friendly Class is the first step and part of the Children Friendly School (CSF) as a UNICEF program and an important Indonesian government policy to prevent the emergence of child bullying behaviour. This study aims to identify needs in the process of developing a Child-Friendly Classroom Management model to anticipate bullying behaviour. This research and development method uses an adaptation of the Rowntree model which includes three stages of the process and data collection techniques using interviews, questionnaires, and observation. The results of this study indicate that the preparation of an effective classroom management guidebook to create child-friendly classes needs to be followed up immediately. Several findings related to teachers' perceptions of classroom management, and child-friendly classes prove that child-friendly classes have not been implemented properly in PAUD institutions, with bullying behaviour still appearing in early childhood in PAUD institutions. PAUD teachers understand that it is important to implement classroom management but so far there has been no manual on how to manage effective classrooms as well as training related to the implementation of effective classroom management. The creation of child-friendly classes is believed to be able to help teachers suppress the emergence of bullying behaviour in early childhood. Keywords: Child-Friendly Classroom Management, Bullying Prevention, Early Childhood Education References: Allday, R. A., Hinkson-Lee, K., Hudson, T. M., Neilsen-Gatti, S., Kleinke, A., & Russel, C. S. (2012). Training General Educators to Increase Behavior-Specific Praise: Effects on Students with EBD. Behavioral Disorders, 37, 87–98. Alsaker, F. D., & Valkanover, S. (2012). The Bernese Program against Victimization in Kindergarten and Elementary School. New Directions for Youth Development, 2012(133), 15–28. https://doi.org/10.1002/yd.20004 Arseneault, L., Walsh, E., Trzesniewski, K., Newcombe, R., Caspi, A., & Moffitt, T. E. (2006). Bullying Victimization Uniquely Contributes to Adjustment Problems in Young Children: A Nationally Representative Cohort Study. PEDIATRICS, 118(1), 130–138. https://doi.org/10.1542/peds.2005-2388 Benedict, E., Horner, R. H., & Squires, J. (2007). Assessment and Implementation of Positive Behavior Support in Preschools. Topics in Early Childhood Special Education, 27, 174–192. Boz, Y. (2008). Turkish student teachers’ concerns about teaching. European Journal of Teacher Education, 31(4), 367–377. https://doi.org/10.1080/02619760802420693 Bradshaw, C. P., & Johnson, R. M. (2011). The Social Context of Bullying and Peer Victimization: An Introduction to the Special Issue. Journal of School Violence, 10(2), 107–114. https://doi.org/10.1080/15388220.2011.557145 Bradshaw, C. P., Sawyer, A. L., & O’Brennan, L. M. (2009). A Social Disorganization Perspective on Bullying-Related Attitudes and Behaviors: The Influence of School Context. American Journal of Community Psychology, 43(3–4), 204–220. https://doi.org/10.1007/s10464-009-9240-1 Bullock, J. R. (2002). Bullying among Children. Childhood Education, 78(3), 130–133. https://doi.org/10.1080/00094056.2002.10522721 Çobanoğlu, F., Ayvaz-Tuncel, Z., & Ordu, A. (2018). Child-friendly Schools: An Assessment of Secondary Schools. Universal Journal of Educational Research, 6(3), 466–477. https://doi.org/10.13189/ujer.2018.060313 Cothran, D. J., Kulinna, P. H., & Garrahy, D. A. (2003). “This is kind of giving a secret away...”: Students’ perspectives on effective class management. Teaching and Teacher Education, 19(4), 435–444. https://doi.org/10.1016/S0742-051X(03)00027-1 Cross, D., Monks, H., Hall, M., Shaw, T., Pintabona, Y., Erceg, E., Hamilton, G., Roberts, C., Waters, S., & Lester, L. (2011). Three‐year results of the Friendly Schools whole‐of‐school intervention on children’s bullying behaviour. British Educational Research Journal, 37(1), 105–129. https://doi.org/10.1080/01411920903420024 Cross, D., Pintabona, Y., Hall, M., Hamilton, G., & Erceg, E. (2004). Validated Guidelines for School-Based Bullying Prevention and Management. International Journal of Mental Health Promotion, 6(3), 34–42. https://doi.org/10.1080/14623730.2004.9721937 Cross, D., Runions, K. C., Shaw, T., Wong, J. W. Y., Campbell, M., Pearce, N., Burns, S., Lester, L., Barnes, A., & Resnicow, K. (2019). Friendly Schools Universal Bullying Prevention Intervention: Effectiveness with Secondary School Students. International Journal of Bullying Prevention, 1(1), 45–57. https://doi.org/10.1007/s42380-018-0004-z Evertson, C. M., & Weinstein, C. S. (2012). Handbook of Classroom Management: Research, Practice, and Contemporary Issues. Fox, B. H., Farrington, D. P., & Ttofi, M. M. (2012). Successful Bullying Prevention Programs: Influence of Research Design, Implementation Features, and Program Components. Research Design, 6, 10. Georgiou, S. N. (2008). Bullying and victimization at school: The role of mothers. The British Journal of Educational Psychology, 78 Pt 1, 109–125. Hammarberg, T. (1998). A School for Children with Rights. UNICEF International Child Development Centre. Hymel, S., & Swearer, S. M. (2015). Four decades of research on school bullying: An introduction. American Psychologist, 70(4), 293–299. https://doi.org/10.1037/a0038928 Johansen, A., Little, S. G., & Akin-Little, A. (2011). An Examination of New Zealand Teachers’ Attributions and Perceptions of Behaviour, Classroom Management, and the Level of Formal Teacher Training Received in Behaviour Management. King, E. (2020). Implications for the child friendly schools policy within Cambodia’s cultural and primary school context. Asia-Pacific Journal of Teacher Education, 48(4), 375–388. https://doi.org/10.1080/1359866X.2019.1645811 Kirves, L., & Sajaniemi, N. (2012). Bullying in early educational settings. Early Child Development and Care,182(3–4), 383–400. https://doi.org/10.1080/03004430.2011.646724 MacSuga, A. S., & Simonsen, B. (2011). Increasing Teachers’ Use of Evidence-Based Classroom Management Strategies through Consultation: Overview and Case Studies. Beyond Behavior, 20, 4–12. Maida, P. (2006). Child-Friendly-School-Manual. UNICEF. Modipane, M., & Themane, M. (2014). Teachers’ social capital as a resource for curriculum development: Lessons learnt in the implementation of a Child-Friendly Schools programme. South African Journal of Education, 34(4), 1–8. https://doi.org/10.15700/201412052105 Monks, C. P., Smith, P. K., & Swettenham, J. (2005). Psychological correlates of peer victimisation in preschool: Social cognitive skills, executive function and attachment profiles. Aggressive Behavior, 31(6), 571–588. https://doi.org/10.1002/ab.20099 Olweus, D. (1994). Bullying at School: Basic Facts and Effects of a School Based Intervention Program. Journal of Child Psychology and Psychiatry, 35(7), 1171–1190. https://doi.org/10.1111/j.1469-7610.1994.tb01229.x O’Neill, S. C., & Stephenson, J. (2011). Classroom behaviour management preparation in undergraduate primary teacher education in Australia: A web-based investigation. Australian Journal of Teacher Education, 36(10). https://doi.org/10.14221/ajte.2011v36n10.3 O’Neill, S., & Stephenson, J. (2012). Does classroom management coursework influence pre-service teachers’ perceived preparedness or confidence? Teaching and Teacher Education, 28(8), 1131–1143. https://doi.org/10.1016/j.tate.2012.06.008 Osher, D., Kelly, D. L., Tolani-Brown, N., Shors, L., & Chen, C.-S. (2009). American Institutes for Research 1000 Thomas Jefferson Street , NW Washington, DC 20007-3835. 13. Perren, S., Stadelmann, S., & Von Klitzing, K. (2009). Child and family characteristics as risk factors for peer victimization in kindergarten. Swiss Journal of Educational Research, 36(1), 13–32. https://doi.org/10.24452/sjer.36.1.4806 Reinke, W. M., Lewis-Palmer, T., & Merrell, K. (2008). The Classroom Check-up: A Classwide Teacher Consultation Model for Increasing Praise and Decreasing Disruptive Behavior. School Psychology Review, 37(3), 315–332. PubMed. Repo, L., & Sajaniemi, N. (2015). Prevention of bullying in early educational settings: Pedagogical and organisational factors related to bullying. European Early Childhood Education Research Journal, 23(4), 461–475. https://doi.org/10.1080/1350293X.2015.1087150 Rigby, K. (2003). Consequences of Bullying in Schools. The Canadian Journal of Psychiatry, 48(9), 583–590. https://doi.org/10.1177/070674370304800904 Rowntree, D. (1994). Preparing Materials for Open, Distance and Flexible Learning: An Action Guide for Teachers and Trainers. Kogan Page. https://books.google.com.jm/books?id=6Tf1kH6MQZ0C Sainio, M., Veenstra, R., Huitsing, G., & Salmivalli, C. (2011). Victims and their defenders: A dyadic approach. International Journal of Behavioral Development, 35(2), 144–151. https://doi.org/10.1177/0165025410378068 Salmivalli, C. (2002). Is there an age decline in victimization by peers at school? Educational Research, 44(3), 269–277. https://doi.org/10.1080/00131880210135331 Saracho, O. (2016). Contemporary Perspectives on Research on Bullying and Victimization in Early Childhood Education. Information Age Publishing, Incorporated. https://books.google.co.id/books?id=dalCDQAAQBAJ Saracho, O. N. (2017). Bullying Prevention Strategies in Early Childhood Education. Early Childhood Education Journal, 45(4), 453–460. https://doi.org/10.1007/s10643-016-0793-y Sempowicz, T., & Hudson, P. (2011). Analysing Mentoring Dialogues for Developing a Preservice Teacher’s Classroom Management Practices. Australian Journal of Teacher Education, 36(8). https://doi.org/10.14221/ajte.2011v36n8.4 Smith, J. D., Schneider, B. H., Smith, P. K., & Ananiadou, K. (2004). The Effectiveness of Whole-School Antibullying Programs: A Synthesis of Evaluation Research. School Psychology Review, 33, 547–560. Sourander, A., Ronning, J., Brunstein-Klomek, A., Gyllenberg, D., Kumpulainen, K., Niemelä, S., Helenius, H., Sillanmäki, L., Ristkari, T., Tamminen, T., Moilanen, I., Piha, J., & Almqvist, F. (2009). Childhood Bullying Behavior and Later Psychiatric Hospital and Psychopharmacologic Treatment. ARCH GEN PSYCHIATRY, 66(9), 9. Tauber, R. T. (2007). Classroom Management: Sound Theory and Effective Practice. Praeger Publishers. https://books.google.la/books?id=XiQFyR41kysC Ttofi, M. M., & Farrington, D. P. (2011). Effectiveness of school-based programs to reduce bullying: A systematic and meta-analytic review. Journal of Experimental Criminology, 7(1), 27–56. https://doi.org/10.1007/s11292-010-9109-1 Ttofi, M. M., & Farrington, D. P. (2012). Bullying prevention programs: The importance of peer intervention, disciplinary methods and age variations. Journal of Experimental Criminology, 8(4), 443–462. https://doi.org/10.1007/s11292-012-9161-0 Unal, Z., & Unal, A. (2012). The Impact of Years of Teaching Experience on the Classroom Management Approaches of Elementary School Teachers. International Journal of Instruction, 5, 41–60. UNICEF. (2007). Implementation Handbook for The Convention on The Rights of The Child (3th Edition). UNICEF. Vaillancourt, T., McDougall, P., Hymel, S., Krygsman, A., Miller, J., Stiver, K., & Davis, C. (2008). Bullying: Are researchers and children/youth talking about the same thing? International Journal of Behavioral Development, 32(6), 486–495. https://doi.org/10.1177/0165025408095553 Vlachou, M., Andreou, E., Botsoglou, K., & Didaskalou, E. (2011). Bully/Victim Problems Among Preschool Children: A Review of Current Research Evidence. Educational Psychology Review, 23(3), 329–358. https://doi.org/10.1007/s10648-011-9153-z Vlachou, M., Botsoglou, K., & Andreou, E. (2014). Bullying/Victimization in Preschool Children. https://doi.org/10.13140/2.1.5086.1764 Vreeman, R. C., & Carroll, A. E. (2007). A systematic review of school-based interventions to prevent bullying. Archives of Pediatrics & Adolescent Medicine, 161 1, 78–88. Witvliet, M., Olthof, T., Hoeksma, J. B., Goossens, F. A., Smits, M. S. I., & Koot, H. M. (2010). Peer Group Affiliation of Children: The Role of Perceived Popularity, Likeability, and Behavioral Similarity in Bullying. Social Development, 19(2), 285–303. https://doi.org/10.1111/j.1467-9507.2009.00544.x Yaşar, M. (2017). Adaptation of General System Theory and Structural Family Therapy Approach to Classroom Management in Early Childhood Education* *. 32.